GROWING RELEVANCE OF QUAD: IMPACT ON INDIA-CHINA RELATIONS - Singh, Amrita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The United States of America (USA), India, Australia, and Japan are the four countries that make up the Quad, commonly known as the "Quadrilateral Security Dialogue" (QSD). Working for a free, open, prosperous, and inclusive Indo-Pacific area is one of the Quad’s main goals. In 2007, the group convened for the first time outside of the Association of Southeast Asian Nations (ASEAN). An alliance of marine democracies is thought to exist. All of the member nations participate in meetings, semi-regular summits, intelligence exchanges, and military exercises to preserve the forum.